Pendampingan Peternak Kelinci Dalam Strategi Pemasaran Melalui Media Sosial Guna Meningkatkan Ekonomi - Fahrudin, Fahrudin; Adi Pranata, Mohammad Sofyan (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2023)
This activity is carried out based on problems obtained in the field, namely the lack of marketing strategies through social media as well as the low economic income of the community from rabbit livestock products. This activity aims to provide knowledge and experience in promoting rabbit livestock products through social media to improve the community's economy. Activities are carried out in stages, starting from the planning stage through implementation and evaluation. The results of this assistance provide experience to the team, which can work together with the community, especially the farmers. It is beneficial for the farmers themselves to increase their knowledge and ability to promote their livestock through social media. Making farmers able to promote and increase the scope of the target market through social media Increase the creativity of farmers in promoting their livestock products. Furthermore, farmers can independently promote and market their livestock products in their respective cages so that they can increase the sales of livestock products optimally.